2019
DOI: 10.2131/jts.44.667
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of cultured mouse testis fragments treated with ethinylestradiol

Abstract: The assessment of xenobiotic-induced testicular toxicity is important in drug development. Nonetheless, in vitro models to test drugs and chemicals that may cause testicular toxicity are lacking, requiring the continued use of animal models for those studies. We previously evaluated an in vitro mouse testis organ culture system using ethinylestradiol (EE), a well-studied testicular toxicant, and demonstrated a dose-dependent relationship between adverse effects to germ cell differentiation and increasing EE co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Comparison of these DEGs with those identified after exposure to other EDCs indicated that 1 to 17 DEGs detected in F1 testes were also deregulated after exposure to the xenoestrogens bisphenol A (BPA) [ 86 ] and EE2 [ 87 ] and to the anti-androgenic EDCs di-2-ethylhexyl phthalate (DEHP) [ 88 ], DDT, and vinclozolin [ 89 ] ( Supplementary Table S9 ). Some genes that were also differentially expressed in F2 testes might be biomarkers of exposure to estrogenic ( Actn3 , Cntnap5b, Kcnk2 , Sall1 ) or anti-androgenic ( Dhrs4 , Fabp3 ) compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of these DEGs with those identified after exposure to other EDCs indicated that 1 to 17 DEGs detected in F1 testes were also deregulated after exposure to the xenoestrogens bisphenol A (BPA) [ 86 ] and EE2 [ 87 ] and to the anti-androgenic EDCs di-2-ethylhexyl phthalate (DEHP) [ 88 ], DDT, and vinclozolin [ 89 ] ( Supplementary Table S9 ). Some genes that were also differentially expressed in F2 testes might be biomarkers of exposure to estrogenic ( Actn3 , Cntnap5b, Kcnk2 , Sall1 ) or anti-androgenic ( Dhrs4 , Fabp3 ) compounds.…”
Section: Resultsmentioning
confidence: 99%